Analysing the influence of Universities’ content strategy on the level of engagement on social media - Paul Capriotti; Carmen Carretón-Ballester; Jose-Carlos Losada-Díaz (Communication & Society (Formerly Comunicación y Sociedad), 2024)
Social media have become a key tool in the institutional communication of universities to disseminate content and establish interaction and dialogue with their publics. Content strategy in social networks is a relevant aspect to inform their audiences about their daily activities and position universities in the digital sphere. This article studies the influence of the different types of content posted by universities on their social networks on the level of engagement of their publics. We conducted a content analysis of more than 90,000 posts by 70 universities in three regions (Europe, the United States and Latin America) on their institutional profiles on three social networks (Twitter, Facebook and LinkedIn). The results show that the level of engagement achieved by the universities’ posts is very low. Universities clearly prioritize institutional content over functional content, and organizational topics are the most published on social networks. Institutional content achieves a higher level of engagement than functional content, and posts on organizational topics have the best level of engagement. Our study might refute the hypothesis that “functional content will generate a higher level of engagement than institutional content on social networks.” Thus, it can be concluded that the combination of content on social networks suggests that universities mainly use social networks to develop an institutional positioning strategy on social media.